2016
DOI: 10.1097/md.0000000000003293
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Specific Local Synchronization Changes in Paroxysmal Kinesigenic Dyskinesia

Abstract: The neurobiological basis of paroxysmal kinesigenic dyskinesia (PKD) is poorly defined due to the lack of reliable neuroimaging differences that can distinguish PKD with dystonia (PKD-D) from PKD with chorea (PKD-C). Consequently, diagnosis of PKD remains largely based on the clinical phenotype. Understanding the pathophysiology of PKD may facilitate discrimination between PKD-D and PKD-C, potentially contributing to more accurate diagnosis.We conducted resting-state functional magnetic resonance imaging on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
4
8
0
Order By: Relevance
“…Conversely, decreased E glob and increased L p were also found in the PKD-M group, indicating a PRRT2 mutationrelated impact on human neurophysiology. Loss-of-function mutations in PRRT2 could lead to synaptic dysfunction; our observation is in accordance with the results of a magnetoencephalographic study which showed that PRRT2-related PKD patients had greater reduction in peak gamma frequency than non-PRRT PKD patients (Z. R. Liu, Miao, Yu, Ding, & Liao, 2016). Consistent with this, the PRRT2 knockout mouse shows impaired functional stability of neuronal networks resulting from short-term plasticity changes, rendering it more susceptible to paroxysmal events triggered by external stimuli (Michetti et al, 2017).…”
Section: Global Topological Alterations In Pkd-m and Pkd-n Patientssupporting
confidence: 91%
“…Conversely, decreased E glob and increased L p were also found in the PKD-M group, indicating a PRRT2 mutationrelated impact on human neurophysiology. Loss-of-function mutations in PRRT2 could lead to synaptic dysfunction; our observation is in accordance with the results of a magnetoencephalographic study which showed that PRRT2-related PKD patients had greater reduction in peak gamma frequency than non-PRRT PKD patients (Z. R. Liu, Miao, Yu, Ding, & Liao, 2016). Consistent with this, the PRRT2 knockout mouse shows impaired functional stability of neuronal networks resulting from short-term plasticity changes, rendering it more susceptible to paroxysmal events triggered by external stimuli (Michetti et al, 2017).…”
Section: Global Topological Alterations In Pkd-m and Pkd-n Patientssupporting
confidence: 91%
“…To the best of our knowledge, this is the first study to examine abnormalities of regional synchronization in a relatively large and typical pediatric TS population using the frequency specificity of ReHo. Several studies demonstrated the frequency specificity of ReHo changes in neurologic and psychiatric disorders, such as paroxysmal kinesigenic dyskinesia (42), schizophrenia (43), and major depression (44). In the present study, significantly increased ReHoin the superior frontal gyrus and superior parietal gyrus of TS children indicated compensatory functions of the frontal-parietal network in the lower frequency bands.…”
Section: Frequency-specific Altered Synchronization In Tssupporting
confidence: 68%
“…The exact biological meaning of ReHo measurements in different frequency bands still needs to be further explored. Several studies demonstrated the frequency dependence of the ReHo changes in different neurological conditions (49-52). Future rs-fMRI research focusing on the biological meaning of ReHo should be conducted in both healthy subjects and patients with specific conditions using spectrum-specific analytical strategies.…”
Section: Analytic Methodsmentioning
confidence: 99%